Pengaruh Penggunaan Media Audio Visual untuk Meningkatkan Motivasi Belajar Kelas V SDN 0509 Janji Lobi Lima - Irma Sari Daulay; Rodiah Hasibuan; Naila Cahaya Safitri; Masitoh Desiana Hrp; Putri Juliana Lubis (Politeknik Kampar, 2026)
This study examines the effect of audio-visual media on the learning motivation of fifth-grade students at SDN 0509 Janji Lobi Lima. The research employed an experimental method using a pretest–posttest design involving one group of students as the research participants. Data were collected through learning motivation questionnaires, achievement tests, and classroom observations conducted during the learning process. The initial observation results indicated that students’ learning motivation was at a moderate level, with a percentage score of 60%. After the implementation of audio-visual media in the instructional activities, students’ learning motivation increased significantly to 89%, which falls into the very high category. Statistical analysis using a t-test revealed a significance value of p < 0.001, indicating a statistically significant difference in learning motivation before and after the use of audio-visual media. These findings demonstrate that audio-visual media have a positive and significant impact on enhancing students’ learning motivation. The use of audio-visual media creates a more engaging, interactive, and meaningful learning environment, which encourages active student participation during the learning process. Therefore, this study recommends the integration of audio-visual media as an effective instructional strategy to improve learning motivation among elementary school students.